EFFECTS OF FEEDING CALCIUM SALTS OF FATTY ACIDS AND TWO LEVELS OF RUMEN UNDEGRADABLE PROTEIN ON PRODUCTION PERFORMANCE OF LACTATING NILI-RAVI BUFFALOES - Rana Yaser Arafat; Saima; Maqsood Akhtar; Muhammad Naveed-ul-Haque; Hifzulrahman (Journal of Animal and Plant Sciences, 2026)
Production performance of lactating Nili Ravi buffalo can be improved with feeding of high rumen undegradable protein (RUP) and calcium salts of fatty acids (Ca-FA). Sixteen multiparous lactating Nili Ravi buffaloes were arranged in a 4×4 Latin square arrangement with (mean ± SD) 11.2±0.76 kg/d of milk yield, 6.41±0.23% milk fat, 583±26 kg of body weight (BW) and 161±24 days in milk (DIM). The dietary treatments were: (1) LPLF-low RUP low fat (2) LPHF-low RUP high fat (3) HPLF-high RUP low fat and (4) HPHF-high RUP high fat. The designed diets provided low and high levels of RUP (27.4% and 38.6%) with low (3.5%) and high fat (4.9%). The duration of each period was 21 days and milk sampling was done twice weekly. Statistical significance among treatment means was evaluated using a p-value of ˂ 0.05. Increasing the RUP and fat supplies increased periodic BW and DMI (P ˂ 0.01) with no interaction effect of RUP × fat (P = 0.51) on BW. Milk yield was increased by 3.8% and 14.0% by increasing RUP and fat supplement respectively. The RUP × fat interaction indicated that increase in milk yield was 51% higher when fat was supplemented with low RUP compared with the high RUP diet (RUP × fat, P < 0.01). Milk fat content was increased with the supplementation of fats by 22.0% and milk fat yield by 39.0% (P < 0.01). Milk protein content and yield increased with the increasing RUP level by 10.8% and 15.7%, respectively. Milk lactose yield increased by 5.8% and 17.0% with increasing RUP and fat levels, respectively (P < 0.01). Feed, nitrogen, and milk efficiencies including 4% fat corrected milk (FCM), energy corrected milk (ECM) and milk energy output were increased (P ˂ 0.01) with HF and HP treatments. Plasma urea nitrogen decreased with HP diet compared with LP diet (P ˂ 0.01), whereas the emission of enteric methane was decreased in HPHF group (P ˂ 0.01). In conclusion, the RUP fraction of 38.6% in concentrate and 300 gram of Ca-FA per animal per day increased the production performance of lactating Nili Ravi buffalo, whereas milk fat increased with fat supplementation and milk protein increased with high RUP supplies.
Keywords: Buffalo; DMI; rumen undegradable protein; rumen by pass fat; milk yield